Interstitial HDR brachytherapy for anal cancer-results and quality of life - Jirkovská, Michaela; Stankušová, Hana; Kindlová, Anna; Jirkovský, Daniel; Lohynská, Radka (Strahlentherapie und Onkologie, 2025)
PURPOSE: While anal cancer is a very rare oncological diagnosis representing less than 2% of lower gastrointestinal tract cancers, the incidence has doubled in the past 20 years. Radical radiochemotherapy with sequential or simultaneous boost is now the standard treatment modality. Interstitial HDR brachytherapy is one of the boost application options. Implementation of new radiotherapy techniques has resulted in improved therapeutic outcomes; however, it is still associated with acute and especially late toxicity. Gastrointestinal disorders and sexual dysfunction are the most frequent factors affecting the long-term quality of cured patients' lives. METHODS: A total of 96 patients consecutively treated between 2000 and 2022 with external beam radio-/chemotherapy and an interstitial brachytherapy boost for histologically verified nonmetastatic anal squamous cell carcinoma were evaluated. The median follow-up time was 15.4 years (range 13.4-17.3 years). The primary objective of the study was to assess local control (LC) and quality of life (QoL). The Czech versions of internationally validated EORTC questionnaires were used to evaluate life quality-the basic EORTC QOL-C30 v.3 and the specific QOL-ANL 27 questionnaire. RESULTS: Local control was 85.5% at 5 years, 83.4% at 10 years, 83.4% at 15 years, and 83.4% at 20 years, and there was no dependence on clinical stage. The most common forms of acute toxicity were cutaneous and hematological but were gastrointestinal for late toxicities. In the evaluation of quality of life, 80.5% of patients alive at the time participated. In the EORTC quality of life questionnaire C30 v.3, patients rated the functional scale score as 86.2 points (standard deviation [SD] = 12.6) and the symptom score as 15.5 points (SD = 12.5). The global health score achieved 68.4 points (SD = 23.6). The most common symptoms were fatigue with 25.6 points (SD = 20.2) and diarrhea with 19.0 points (SD = 27.8). In the QOL-ANL 27 questionnaire, symptom scales assessing bowel symptoms were scored 27.5 points (SD = 19) in non-stoma patients and 11.9 points (SD = 17.2) in stoma patients. In the single-item symptom scales, the highest scores were rated for frequency of urination with 26.4 points (SD = 30.8), need to be close to a toilet with 22.4 points (SD = 27.3), and self-cleaning more often with 25.3 points (SD = 31.8). In the functional scales assessing sex life and interest, men and women reported scores of 45.2 (SD = 23) and 45.5 points (SD = 19), respectively. CONCLUSION: Boost with interstitial HDR brachytherapy is an established safe method of anal cancer treatment, with excellent results and limited late toxicity. Functioning scales were rated relatively highly in QoL questionnaires, and the overall global health score was comparable to published data. Gastrointestinal difficulties, fatigue, and sexual dysfunction dominated the symptom scales in our cohort.
Keywords: Surveys and Questionnaires; radiační poranění; Radiochemotherapy; Humans; lidé středního věku; Anus Neoplasms; Quality of Life; Female; Aged; Radiotherapy Dosage; dospělí; Radiation Injuries; celková dávka radioterapie; výsledek terapie; senioři; lidé; kvalita života; nádory anu; průzkumy a dotazníky; Interstitial brachytherapy; Adult; Late toxicity; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Long-term outcomes; Squamous cell carcinoma of the anus; Aged, 80 and over; senioři nad 80 let; spinocelulární karcinom; Carcinoma, Squamous Cell; mužské pohlaví; brachyterapie; následné studie; Brachytherapy